The Impact of Embeddedness on the Economic Performance of Firms - Mačerinskas, Jogaila; Pakalnienė, Akvile (Ekonomika, 2004)
This paper presents the main existing notions of embeddedness and emphasizes its impact on the economic performance of a firm. Many scientists have been trying to elaborate this confusingly polyvalent concept, but still there is now a plethora of meanings and definitions of what embeddedness might be or consist of. Different distinctions between the dimensions and levels of embeddedness exist, the most popular among them being the micro and macro level distinction of embeddedness. In this paper, attention is focused on the micro level and the effects that embeddedness exerts on the performance of firms. The main positive and negative features of embeddedness in the economic performance of a firm are presented.